Persistence and adherence of biologics in US patients with psoriatic arthritis: analyses from a claims database. (27th March 2019) - Oelke, Kurt R; Chambenoit, Olivier; Majjhoo, Amar Q; Gray, Stephani; Higgins, Kate; Hur, Peter
Aim: To evaluate the persistence and adherence of subcutaneous biologics in patients with psoriatic arthritis (PsA).Patients & methods: Psoriatic arthritis patients who initiated adalimumab, certolizumab pegol, etanercept, golimumab or secukinumab between 15 January 2016 and 31 July 2017 were identified in the Truven Databases. Outcomes included discontinuation rate, persistence and adherence over 12 months.Results: Of 1558 patients included, the 12-month discontinuation rate was lowest with secukinumab (36.5%), followed by adalimumab, golimumab, etanercept and certolizumab pegol (42.6–51.6%). Mean persistence ranged from 240.7 (certolizumab pegol) to 282.8 days (secukinumab). The mean proportion of days covered was highest with secukinumab (0.67) and lowest with certolizumab pegol (0.49).Conclusion: Patients who initiated secukinumab had the lowest discontinuation rate and highest persistence and adherence over 12 months.